Codes under scrutiny. The cases of municipality of Lanús (province of Buenos Aires) and of municipality capital (province of San Juan) (2008-2022), Argentina - Galgano, Matías N.; Alcaide-Olivera, María Sol (Revista de Estudios Andaluces, 2025)
The present article aims to describe the current state of building and/or urban planning codes (CE), as well as complementary regulations, in the municipalities of Lanús (Province of Buenos Aires) and the Capital Department (Province of San Juan) in Argentina. While the methodology did not follow a comparative approach, the symmetries and asymmetries between the units of analysis (CE) were examined using common dimensions. Through a qualitative methodology, the study highlights the main points of intersection and the gaps that prevent local governments from becoming active participants in comprehensive urban development. This work serves as an introductory contribution, based on case studies, to the theoretical-methodological approaches to regulations and urban-territorial planning.